2010
DOI: 10.2174/1745017901006010126
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Effects of Social Support in Major Depression Epidemiology

Abstract: Background:The clinical course and epidemiology of major depressive episodes (MDEs) may be influenced by reciprocal interactions between an individual and the social environment. Epidemiological data concerning these interactions may assist with anticipating the clinical needs of depressed patients.Methods:The data source for this study was a Canadian longitudinal study, the National Population Health Survey (NPHS), which provided 8 years of follow-up data. The NPHS interview included a brief diagnostic indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
2
30
1
Order By: Relevance
“…Stigma and disclosure concerns are particularly important to the experiences of those living with depression because stigma can interfere with help seeking and treatment adherence (Wahl, 2012) and because social support is such a critical component of the illness (Patten et al, 2010). In particular, knowledgeable third parties like friends or workplace administrators are often privy to information about a patient's tendency to disclose or conceal his or her illness, and this information may be both a constant reminder about the illness and a salient piece of information about it.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and disclosure concerns are particularly important to the experiences of those living with depression because stigma can interfere with help seeking and treatment adherence (Wahl, 2012) and because social support is such a critical component of the illness (Patten et al, 2010). In particular, knowledgeable third parties like friends or workplace administrators are often privy to information about a patient's tendency to disclose or conceal his or her illness, and this information may be both a constant reminder about the illness and a salient piece of information about it.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, changes of health status might be accompanied by changes of the psychological gender (Behar, de la Barrera, & Michelotti, 2001;Gale-Ross et al, 2009;Kowalczyk et al, 2012;Ku et al, 2002;Patten, Williams, Lavorato, & Bulloch, 2010;Radley et al, 2000;Sajatovic, Micula-Gondek, Tatsuoka, & Bialko, 2011;Wysocka-Bobryk, Procner, & Tchórewska, 2001). It has been also reported that even apparently adverse psychological changes (for instance developing depression) can be interpreted as an adaptation to new, more difficult life conditions (Andrews & Thomson, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is alarming because the U type among healthy people is characterized by the highest level of stress (known as a risk factor for cardiovascular diseases) and by the highest risk of developing depression, which is a common comorbidity of HF (Drohomirecka, Jankowska, Banasiak, & Ponikowski, 2008;Jankowska et al, 2010;Lipińska-Grobelny, 2008;Patten et al, 2010;Prakash et al, 2010). In other words, type U can be interpreted as the least favorable type in the context of general health status and emotional comfort.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the set of dysfunctional symptoms, such as irritability, intolerance, and arrogance present in the acute phases of mania or hypomania, decreases one's capacity in maintaining the ability to deal with others, and, subsequently, may contribute to the reduction of social support. This bidirectional relation should be highlighted [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%